Seismic site period studies for nonlinear soil in the city of Ottawa, Canada. Issue 136 (September 2020) - Motazedian, D.; Torabi, H.; Hunter, J.A.; Crow, H.L.; Pyne, M.
Abstract: Site period maps at various strain levels were developed for the combined cities of Ottawa and Gatineau in eastern Ontario and western Quebec. These maps were developed to support earthquake response studies in areas containing post-glacial, soft, silty-clayey sediments, which comprise 60% of the urban areas. Approximately 21, 700 boreholes and over 1000 surface and downhole geophysical measurements were utilized to prepare the maps. The maps include the following: 1) A T0, ESL map is based on an equivalent single-layer modelling method (ESL) as described in the National Building Code of Canada using the 4H/V approach. 2) A T0, HVSR map is based on the micro-tremor HVSR method, which systematically deviates from T0, ESL for weak motion. Such variances between the calculated T0, ESL and measured T0, HVSR may be associated with significant shear wave velocity-depth gradients in the near-surface soft sediments. 3) A T0, 100 map is based on finite element modelling at the 100 cm/s/s level of shaking (0.1 g) at the onset of the "gray zone" between the linear and nonlinear soil responses. 4) A T0, 400 map is developed from a finite element model at the 400 cm/s/s level of shaking (0.4 g being the "design" earthquake for the city of Ottawa) This model evaluates the effect of nonlinear soft soil behaviour. The differences between these maps were examined and compared. The results indicated that nonlinear soil response at high levels of shaking strongly altered the resonance response toward much longer fundamental periods over large areas within the two cities. Highlights: Site period maps at various strain levels for Leda clay . A map based on the micro-tremor HVSR method. A map based on finite element modelling at the 100 cm/s/s level of shaking. A map based on finite element modelling at the 400 cm/s/s level of shaking. Effects of nonlinear soft soil behaviour .